PREPARATION AND EVALUATION OF LAFUTIDINE NANOEMULSION AS ORAL DELIVERY SYSTEM - KHUDHAIR ALBO HAMRAH, KARRAR T.; NEAMAH AL-SHAIBANI, ABULFADHEL J.; F. ABDULRAZZAQ, INAS (International Journal of Applied Pharmaceutics, 2024)
Objective: Lafutidine is a histamine (H2) receptor antagonist utilized for the treatment of gastric ulcer. Its oral bioavailability is low due to poor water solubility and an extensive first-pass hepatic. So, the present work aims to formulate and characterize of an oil in water (o/w) nanoemulsion of lafutidine as oral liquid dosage form and this could enhance drug solubility and improve its bioavailability. Methods: The pseudo-ternary phase diagrams were constructed via titration method. The diagram plots derived from oil, various ratios of surfactant and co-surfactant (S mix), and double distilled water. The selected optimized lafutidine nanoemulsions formula was determined via a variety of investigational studies like particle size, polydispersity index (PDI), zeta potential, pH, drug content and an in vitro drug release. Results: Characterization studies revealed that the optimum formula of nanoemulsions was (NE5), which consist of 0.2% of lafutidine, 30 % of surfactant and co-surfactant (S mix) (3:1), which mean (22.5%of tween 20:7.5% of polyethylene glycol 200 (PEG 200), 10% of peppermint oil and 59.4% of double distilled water. The optimized formula exhibited droplets size (62.56-96.2 nm), PDI (0.11), good pH value (7.1), zeta potential (-32.2 mV), high drug content (99.2%), in vitro release of lafutidine was significantly higher (P<0.05) for NE5. Scanning probe microscopy (SPM) revealed that the droplets size of NE5 was in nano-scale. Conclusion: It is possible to conclude that the optimized formula (NE5) was promised formula of nanoemulsion for increasing the orally delivered lafutidine bioavailability.